Using Play to Improve Infant Sleep: A Mixed Methods Protocol to Evaluate the Effectiveness of the Play2Sleep Intervention - Keys, Elizabeth; Benzies, Karen M.; Kirk, Valerie; Duffett-Leger, Linda (Frontiers in Psychiatry, 2018)
Background: One in four Canadian families struggle with infant sleep disturbances. The aim of this study is to evaluate Play2Sleep in families of infants with sleep disturbances. In addition to parental education on infant sleep, Play2Sleep uses examples from a video-recorded, structured play session with mothers and fathers separately to provide feedback on parent-infant interactions and their infant's sleep-related social cues. The quantitative phase will answer the research question: Does one dose of Play2Sleep delivered during a home visit with mothers and fathers of infants aged 5 months reduce night wakings at age 7 months? The qualitative phase will answer the research question: What are parental perceptions of family experiences, processes, and contexts related to Play2Sleep and infant sleep? The overarching mixed methods research question is: How do parental perceptions of family experiences, processes, and contexts related to infant sleep explain the effectiveness of Play2Sleep? Method and analysis: An explanatory sequential mixed methods design will be used. In the quantitative phase, a randomized controlled trial and RM-ANOVA will compare night wakings in infants whose parents receive Play2Sleep versus standard public health nursing information. Sixty English-speaking families (mothers and fathers) of full-term, healthy, singleton, 5-month old infants who perceive that their infant has sleep disturbances will be recruited. The primary outcome measure will be change in the number of night wakings reported by parents. The qualitative component will use thematic analysis of family interviews to describe parental perceptions and experiences of infant sleep. Mixed methods integration will use qualitative findings to explain quantitative results. Discussion: Play2Sleep is a novel approach that combines information about infant sleep with personalized feedback on parent-infant interactions and infant cues. Including fathers and mixed methods should capture complex family experiences of infant sleep disruptions and Play2Sleep. If effective, Play2Sleep has possible application for preventing infant sleep disturbance and tailoring for other populations. Ethics and dissemination: The study has been approved by an institutional review board (REB15-2652). Dissemination will include local and international presentations, peer-reviewed publications, and a social media campaign designed for parents and clinicians. ClinicalTrials.gov Identifier: NCT02742155. Registered on 2016 April 23